The Effect Of Cold Temperatures On The Preservation Of Mangoes - Maulana, Ade Septia; Mecca Dewi, Kamila; Nurul Azizah, Nazwa; Allaia, Rainta; Chandra, Yudhistira (Jurnal Agrosci, 2025)
The phenomenon of mangoes being easily damaged due to high water content requires a preservation method to extend their shelf life without losing their nutritional qualities. The purpose of this study is to examine the effect of cold temperatures on the physical quality of mangoes, including taste, texture, color, and aroma. The study was conducted using a qualitative experimental method with organoleptic tests on four treatment groups: whole mangoes and slices at cold temperature (±4°C) and room temperature (±23°C). The assessment is carried out subjectively using a scale for each physical quality parameter. The findings of the study proved that storage at low temperatures for six days slowed down the decay and retained the texture of the mango but led to a decrease in sweetness, aroma intensity, and a paler color change. In contrast, storage at room temperature retains taste, color, and aroma better, although the texture is slightly coarse. Mango slices are more susceptible to damage than whole mangoes at both temperatures. This research provides recommendations for mango storage methods, namely room temperature to maintain the natural quality of the fruit in a short time and cold temperature as a temporary alternative to slow down damage.